Impact and Integration of Culturally Centered American Indian/Alaska Native Practices and Training During COVID-19 on Tele-Behavioral Substance Use Treatment: Protocol for a Community-Derived Mixed Methods Study - Neshay S. D’Silva; Melissa Wheeler; Juliette Roddy; Shane Haberstroh; Julie A. Baldwin; Ramona N. Mellott; Chesleigh Keene (Genealogy)
(1) Background: American Indian and Alaska Native (AI/AN) communities faced disproportionate COVID-19 infection rates and a higher prevalence of substance use disorders (SUDs). Telehealth emerged as a key strategy to address these health disparities. (2) Objective: In response to a call to action from an urban Indian organization (UIO), our multidisciplinary team conducted a community-based participatory study to (1) examine the integration of Native practices in SUD treatment during COVID-19, and (2) develop provider training modules based on these findings. (3) Methods: Using a mixed methods approach, we conducted semi-structured interviews with six community SUD providers, surveyed 91 clients, and analyzed 278 de-identified health records from the UIO Native-serving facility in the Southwest U.S. from May 2020 to May 2021. (4) Results: As of October 2024, analysis of Aim 1 is ongoing. With UIO engagement, findings from Aim 1 are being translated into training modules for Aim 2. (5) Conclusion: This community-driven study lays the foundation for future research on Indigenous mental well-being, centering strength, resilience, and cultural knowledge in substance use treatment. Findings will be disseminated through presentations and publications with Native and non-Native communities, treatment centers, educators, and leaders. Future studies will assess the effectiveness of the training modules among clinicians.